USING FACEBOOK BRAND COMMUNITIES TO ENGAGE CUSTOMERS: A NEW PERSPECTIVE OF RELATIONSHIP MARKETING - Ul Islam, Jamid; Zaheer, Asma (PEOPLE: International Journal of Social Sciences, 2016)
With the advent of digital age, engaging customers on social networking sites has become a crucial marketing activity of companies. This study, through a questionnaire survey of 320 students in India, explores the role of customer engagement in enhancing customer relationships on Facebook brand communities so as to add value to the company. The direct effect of customer participation on word of mouth as well as an indirect effect through the mediation of customer engagement is investigated. The results show a positive relationship between customer participation and word of mouth, results also delineate that customer participation leads to customer engagement, which in turn plays a crucial role in generating word of mouth. This study is the first of its kind in Indian context.